An in-depth study of the antimicrobial spectrum activity of a number of new phosphonium derivatives of naphthalene - A. V. Humenna; D. V. Rotar; N. D. Yakovychuk; O. O. Blinder; S. Ye. Deineka (Zaporožskij Medicinskij Žurnal)
An intensive use of antibiotics and antiseptics is a part of modern principles of treatment and prevention of infectious diseases. Excessive and uncontrolled use leads to the emergence of antibiotic-resistant strains of microorganisms, which necessitates the search for new antimicrobial alternatives. The study of phosphonium derivatives of naphthalene is one of the promising directions for the detection of new highly active antimicrobial agents.